2020
DOI: 10.1001/jama.2020.10009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Acetaminophen on Postoperative Hypoxemia After Abdominal Surgery

Abstract: for the FACTOR Study Group IMPORTANCE Opioid-induced ventilatory depression and hypoxemia is common, severe, and often unrecognized in postoperative patients. To the extent that nonopioid analgesics reduce opioid consumption, they may decrease postoperative hypoxemia.OBJECTIVE To test the hypothesis that duration of hypoxemia is less in patients given intravenous acetaminophen than those given placebo. DESIGN, SETTING, AND PARTICIPANTS Randomized, placebo-controlled, double-blind trial conducted at 2 US academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…This may be a benefit from the decreased use of opioids during the postoperative period. A recent large sample and high-quality randomized clinical trial reports showed that the incidence of PONV in patients without intervention with opioid-based patient-controlled intravenous analgesia after abdominal surgery was 44.3% [ 32 ]. A reduction in the occurrence of PONV contributes to postoperative recovery and is consistent with ERAS.…”
Section: Discussionmentioning
confidence: 99%
“…This may be a benefit from the decreased use of opioids during the postoperative period. A recent large sample and high-quality randomized clinical trial reports showed that the incidence of PONV in patients without intervention with opioid-based patient-controlled intravenous analgesia after abdominal surgery was 44.3% [ 32 ]. A reduction in the occurrence of PONV contributes to postoperative recovery and is consistent with ERAS.…”
Section: Discussionmentioning
confidence: 99%
“…This may be a result of less opioid usage during the postoperative period. The results of a recent RCT with a large sample indicated that the incidence of PONV was 44.3% after general anesthesia [ 47 ]. Effective prevention of PONV is important in the implementation of enhanced recovery after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Because pain was assessed as a secondary endpoint, no definitive conclusions can be drawn. 16 Further studies are needed to demonstrate consistent benefit for the use of IV acetaminophen in this population.…”
Section: Colorectal Surgerymentioning
confidence: 97%